IoT based tracking cattle healthmonitoring system using wireless sensors - Jai Ganesh Rajendran; Manjunathan Alagarsamy; Vaishnavi Seva; Paramathi Mani Dinesh; Balamurugan Rajangam; Kannadhasan Suriyan (Bulletin of Electrical Engineering and Informatics, 2023)
Controlling the health of dairy cows is crucial for increasing global dairy food output. Dairy farmers are losing faith in the sector as cows suffer from a range of health issues, disease outbreaks that are unpredictable, and expensive breeding expenses. As a consequence, farmers must use efficient technology techniques for cow health monitoring in order to enhance milk output. This study looked at a range of wireless sensor-based automated dairy cow health monitoring systems. The fundamental purpose of wireless sensor network (WSN) based smart surveillance systems in agricultural optimization is to follow the health of dairy cows on a continual basis. This monitoring gadget must be installed in both local and remote farm areas so that interested farmers may monitor their cattle's movements throughout the day from several places. The data collected by the automated system would be kept in a database. Farmers may then obtain data using farm automation to execute effective farm management techniques. Furthermore, WSN is a low-cost device created exclusively for identifying illnesses in dairy cows. This achievement in sophisticated technology agricultural automation would assist to boost productivity by reducing human involvement. This article summarises all livestock tracking techniques, as well as the issues and challenges that they confront.